The Measurement of Nonlinear Distortion Using Broadband Noise - DOBRUCKI, Andrzej; SICZEK, Rafał (Archives of Acoustics, 2008)
The method of measurement of nonlinear distortions in loudspeakers using digital filters has been presented. Using MATLAB software packet developed by MathWorks it is possible to design necessary filters. The Simulink packet has been used for simulation of the measuring process. The level of the residual noise caused by finite slope of the filters has been determined. The static polynomial function has been applied for both: simulation and the measured objects.